How the human-machine interchange will transform business operations. Issue 2 (18th March 2019) - Butner, Karen; Ho, Grace
Abstract : Purpose: Machine learning is beginning to transform the way businesses organize their operations and benefit from technology investments. Design/methodology/approach: To learn more about how far along organizations are in deploying intelligent automation and in developing plans and strategies for its adoption, the IBM Institute for Business Value, in collaboration with Oxford Economics surveyed and interviewed 550 technology and operations executives. Findings: The primary purpose of intelligent automation is to augment employees' skills, experience and expertise, extending the human mind in ways that allow for higher productivity, creative problem-solving and more engaging jobs for employees. Practical implications: Automation is not a plug-and-play solution: companies cannot just buy the technology, flip the switch and watch robots run the business without any human intervention. Originality/value: This recent survey of operations executive with specific knowledge of their companies plans provides insights into best practice. Executives believe that layering new technologies on top of old business processes is apt to be less productive ? and less cost-effective ? than rethinking processes to make the most of intelligent automation. Executives must optimize workflows for automation; this means envisioning the end result, enabling it through logical steps and prototyping the process ? then repairing as necessary before scaling.